Geographical longitude/latitude and lightning characteristics in monsoon- season Benin thunderstorms - ADECHINAN, A. Joseph; HOUNGNINOU, BODOUN ETIENNE; KOUGBEAGBEDE, Hilaire; GUEDJE, K. François (My University, 2019)
In this study, the relationship between the geographical longitude/latitude and lightning characteristics detected during the monsoon-season in north of Benin is investigated. The data used for this purpose are collected by the Lightning Detection Network and their analyses focused on the density, polarity and intensity. The main results show that intracloud and cloud-to-ground lightning have similar characteristics. The dynamics of lightning occurrence irrespective of their type or their polarity are contrary to their intensity. The variation of lightning density is influence by orographic effect. The lightning density shows a strong relationship with geographical longitude and latitude. Moreover, the lightning activity is weak in the morning but becomes intense in the afternoon with a main peak displayed around 15:00 UTC for cloud-to-ground lightning and 17:00 UTC for intracloud lightning. The variation of intracloud as a function of altitude follows the normal law with the maximum occurrence displayed around 11.5 km in August and the average intensity of these discharges decreases with altitude.
Keywords: lightning; characteristics; geographical; longitude/latitude; Benin; Relationship.